Catalytic co-pyrolysis of blended biomass plastic mixture using synthesized metal oxide(MO)-dolomite based catalyst - Harith N.; Hafriz R.S.R.M.; Arifin N.A.; Tan E.S.; Salmiaton A.; Shamsuddin A.H. (Elsevier B.V., 2023)
Calcium carbonate; Catalysts; Fluid catalytic cracking; Fluidized beds; Fruits; High density polyethylenes; Lime; Magnetite; Nickel oxide; Plastic recycling; Zeolites; Bio-oils; Blended biomass; Copyrolysis; Dolomite catalyst; Empty fruit bunch; Empty fruit bunches; High-density polyethylene; High-density polyethylenes; Oxygenated compounds; ]+ catalyst; Dolomite